Countering online propaganda and extremism the dark side of digital diplomacy - Bjola, Corneliu; Pamment, James (Routledge, 2019)
"Exploring the 'dark side' of digital diplomacy, this volume highlights some of the major problems facing democratic institutions in the West and provides concrete examples of best practice in reversing the tide of digital propaganda"--
Keywords: Mass media and propaganda; Mass media and international relations; Internet and international relations; Propaganda, International; Information warfare; Extremist Web sites; Social media / Political aspects; Internet / Political aspects; Bekämpfung; Internationale Politik; World Wide Web; Kommunikation; Manipulation; Internet; Propaganda; Social Media; Radikalismus; Öffentliche Meinung; Desinformation; Terrorismus; Aufsatzsammlung